2011
DOI: 10.1007/s11010-011-1187-5
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of mechano-growth factor expression by myofibrillar proteins in murine myoblasts and myotubes

Abstract: Mechano-growth factor (MGF) is a product of alternative splicing of the insulin-like growth factor 1 (IGF-1) mRNA. MGF is known to stimulate myoblast proliferation and to protect neurons and cardiomyocytes from apoptosis. MGF expression is dramatically increased in response to mechanical stimuli and tissue damage. The mechanisms of induction of MGF expression are as yet imperfectly understood. There is certain evidence that some protein factors able to stimulate MGF synthesis in normal myoblasts are released f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…Here, we have shown that, in agreement with a previous study (Kravchenko et al , ), MGF‐Ct24E can promote cell viability after nerve injury in the primary cultured cortical neurons, thus exhibiting a protective role against neuronal apoptosis. Furthermore, we demonstrate that MGF‐Ct24E can promote axonal connection and elongation (Figure ), but cell density decreased significantly after MGF‐Ct24E treatment at 0.05, 0.1, 0.5 and 1.0 μg/ml.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Here, we have shown that, in agreement with a previous study (Kravchenko et al , ), MGF‐Ct24E can promote cell viability after nerve injury in the primary cultured cortical neurons, thus exhibiting a protective role against neuronal apoptosis. Furthermore, we demonstrate that MGF‐Ct24E can promote axonal connection and elongation (Figure ), but cell density decreased significantly after MGF‐Ct24E treatment at 0.05, 0.1, 0.5 and 1.0 μg/ml.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies of MGF and its E‐domain peptide were mainly focused on bone transplantation or rehabilitation, and fewer reports have been concentrated on neuroscience (Kravchenko et al , ; Riddoch‐Contreras et al , ). MGF and MGF‐Ct24E have been implicated in neuronal development, maintenance and neuroprotection, but the certain mechanism needs to be investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding allows us to conclude that mRNA expression of MGF (IGF‐1Ec) in trained muscle depends on the exercise intensity (comparison of MI and HI) and does not depend on the metabolic stress (comparison of MIR and MI). We have shown previously that myofibrillar proteins (such as myomesin 1, myosin‐binding protein C, and titin) released from damaged cells stimulate MGF expression at both the mRNA and protein levels in primary murine myoblasts or differentiated in vitro myotubes . It is possible to speculate that, in our study, HI induced degradation of myofibrillar proteins, which may stimulate MGF gene expression.…”
Section: Discussionsupporting
confidence: 53%
“…This effect persisted for 24 h, where Igf1 gene expression increased by 4-fold compared with the control (63). Similarly, in studies of muscle cells, IGF-1 gene and protein expression increased in response to activation of the cAMP/PKA pathway (64,65). Therefore, we assessed whether PTH enhances GHR activation by increasing Ghr, Igf1,o rIgf1r gene expression in IDG-SW3 osteocyte-like cells.…”
Section: Pth Sensitizes Osteocytes To Ghmentioning
confidence: 93%